Adipocyte Gi signaling is essential for maintaining whole-body glucose homeostasis and insulin sensitivity - Lei Wang (Nature Portfolio, 2020)
Gs-coupled receptor signaling is well known to modulate adipocyte metabolism, but the role of Gi-coupled receptors in adipose tissue is less well understood. Here the authors show that signaling via Gi-type G proteins expressed by adipocytes is essential for maintaining proper blood glucose homeostasis.